Implementasi Etika Bisnis Islam dalam Strategi Promosi Produk Asuransi Takaful - Junia Farma; Khairil Umuri (Cakrawala: Jurnal Studi Islam, 2020)
Asuransi Takaful is a company that offers risk insurance services. The company exhibits strict religious compliance in its operation, and does not engage in any prohibited business. However, the strategies used in promoting the products are suspected to violate Islamic business ethics. This study is conducted to examine the implementation of the concept of Islamic business ethics in the promotion strategies at PT Asuransi Takaful of Banda Aceh Branch. This is a field research which uses a descriptive qualitative approach. The finding shows that PT. Asuransi Takaful has implemented tawḥid, ‘adl, ikhtiyār, farḍ, and iḥsān in their promotion strategies